Treatment effects on event-related EEG potentials and oscillations in Alzheimer's disease - Yener, Görsev; Hünerli Gündüz, Duygu; Yıldırım, Ebru; Aktürk, Tuba; Başar Eroğlu, Canan; Bonanni, Laura; Del Percio, Claudio; Farina, Francesca; Ferri, Raffaele; Güntekin, Bahar; Hajós, Mihály; Ibáñez, Agustín; et al. (Elsevier B.V., 2022)
Alzheimer's disease dementia (ADD) is the most diffuse neurodegenerative disorder belonging to mild cognitive impairment (MCI) and dementia in old persons. This disease is provoked by an abnormal accumulation of amyloid-beta and tauopathy proteins in the brain. Very recently, the first disease-modifying drug has been licensed with reserve (i.e., Aducanumab). Therefore, there is a need to identify and use biomarkers probing the neurophysiological underpinnings of human cognitive functions to test the clinical efficacy of that drug. In this regard, event-related electroencephalographic potentials (ERPs) and oscillations (EROs) are promising candidates. Here, an Expert Panel from the Electrophysiology Professional Interest Area of the Alzheimer's Association and Global Brain Consortium reviewed the field literature on the effects of the most used symptomatic drug against ADD (i.e., Acetylcholinesterase inhibitors) on ERPs and EROs in ADD patients with MCI and dementia at the group level. The most convincing results were found in ADD patients. In those patients, Acetylcholinesterase inhibitors partially normalized ERP P300 peak latency and amplitude in oddball paradigms using visual stimuli. In these same paradigms, those drugs partially normalize ERO phase-locking at the theta band (4–7 Hz) and spectral coherence between electrode pairs at the gamma (around 40 Hz) band. These results are of great interest and may motivate multicentric, double-blind, randomized, and placebo-controlled clinical trials in MCI and ADD patients for final cross-validation.
Keywords: Alzheimer; Biomarker; Dementia; EEG; EROs; ERPs; Event-related; Mild Cognitive Impairment; Monitoring; Oscillations; P300; Treatment